SOSIALISASI PEMBUATAN MEREK PRODUK UKM DI KELURAHAN PEDURUNGAN SEMARANG - Emaya Kurniawati; Sri Yuni Widowati; Aprih Santoso (Publisher UPT P2M Politeknik Negeri Malang, 2021)
The Community Service Program that we will carry out is located at RT 14 RW 09 Pedurungan Tengah Village with the target audience of UKM in the RT! 4 RW 09 area. Pedurungan Tengah Village, Semarang. These SMEs produce food products whose sales are increasing day by day and have a wider range of consumers. Products that have been sold in the market and are well known do not yet have a name or brand, SMEs do not understand the importance of a brand for a product. They only care about the important product sold. In this Community Service activity to introduce more about the importance of a brand for a product, socialization and an explanation of the importance of the name or product brand are given to differentiate it from other similar products.From the results of this dedication, it is hoped that participants will be able to understand the importance of brands for products that have been produced and make them start thinking about or designing names or brands for their products.